CROATIAN DICTIONARY HERITAGE - COLLECTION OF OLD CROATIAN DICTIONARIES IN DIGITAL FORM - Boras, Damir (2004)
At the turn of the 16th to the 17th century numerous dictionaries were published in Croatia – starting with F. Vrančić's, J. Mikalja’ s J. Habdelić’ s, I. Belostenec’ s etc. which with other dictionaries written up to the present time, make the invaluable Croatian linguistic heritage. Most of those dictionaries are multilingual. Although numerous experts have used the above mentioned dictionaries, none of these older dictionaries has been prepared in digital form and their structure has not been completely analysed. The dictionaries which are already analized and which are to be analysed in the scientific project named Croatian dictionary heritage and dictionary knowledge presentation are all multi-lingual ones covering Latin, Italian, German, Hungarian as well as Croatian language (including its old Kajkavian dialect which is a good basis for research on old Slovenian language). As today's Italy, Slovenia, Austria, Hungary and Croatia were (entirely or partly) parts of the Austro-Hungarian Empire with the same governmental, and in most cases educational system, those dictionaries contain elements important for linguistic, cultural and historic comparisons in those countries as well. Thus, tools and corpora presented in this poster will be valuable source of data for further research on development of all mentioned languages and cultures. It is important to note that such researches are not many and are of most valuable concern for the experts in other countries in the region. The scientific project Croatian dictionary heritage and dictionary knowledge presentation led by professor Damir Boras is financially supported both by UNESCO and by the Croatian Ministry of Science and Technology.
Projekt MZOS
ENG